MISE EN PLACE D’UN SYSTEME DISTRIBUE DE PUBLICATION DES CURSUS ACADEMIQUES DES ETUDIANTS - ESOKELI , Laurent KOMPANI; SINGA, Nathan IUNGBI (IJRDO -Journal of Computer Science Engineering, 2023)
The implementation of a distributed system for publishing students’ academic courses aims to facilitate and standardize the dissemination of information on students’ academic paths. The main objective of this system is to provide a secure and reliable platform where students can view their academic history. Relevant information includes degrees earned, grades, research projects, internships completed, publications, and skills acquired. To set up such a system, it is essential to take into account several aspects. First of all, the confidentiality and security of student data must be guaranteed. It is necessary to implement strict access control and data encryption mechanisms to protect sensitive information. Then, it is important to define a standardized publication framework that allows students to present their courses in a coherent and understandable way for third parties. This may include information presentation models, metadata tags and data interchange standards. In addition, collaboration between the various players in the system is essential. Universities should cooperate to share student academic data securely. Employers and other organizations should also be actively involved in using this system to verify and validate student academic background information. Finally, it is crucial to put in place data verification and validation processes to ensure the accuracy and credibility of the information published. Academic authorities can play a key role in verifying the validity of degrees and certifications.